Gamification elements in software engineering context [Elementos de gamificación en el contexto de ingeniería de software] (2020)
The potential of gamification in the context of software engineering is based on the hypothesis that it can help to face the challenges related to the treatment of social and human factors. Some of these challenges influence the engagement, the communication and the motivation of software development teams, with an impact on their productivity. However, gamification is a recent research area. Therefore, it is necessary to identify essential gamification elements for the construction of gamification strategies that help to face these challenges. This paper presents an analysis of the gamification elements, based on a systematic literature review. The purpose is to determine viable gamification elements to belong to a catalog. The selection of elements is made using techniques to identify the patterns in the gamification elements most used in this context. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.